2019
DOI: 10.1103/physreve.99.062126
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty relations in stochastic processes: An information inequality approach

Abstract: The thermodynamic uncertainty relation is an inequality stating that it is impossible to attain higher precision than the bound defined by entropy production. In statistical inference theory, information inequalities assert that it is infeasible for any estimator to achieve an error smaller than the prescribed bound. Inspired by the similarity between the thermodynamic uncertainty relation and the information inequalities, we apply the latter to systems described by Langevin equations and derive the bound for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 46 publications
0
96
0
Order By: Relevance
“…A connection between discrete and continuous time uncertainty relations is shown in [34]. One can also see similar uncertainty relations in the context of discrete processes [35], multidimensional systems [36], Brownian motion in the tilted periodic potential [37], general Langevin systems [38], molecular motors [39], run and tumble processes [40], biochemical oscillations [41], interacting oscillators [42], effect of magnetic field [43], linear response [44], measurement and feedback control [45], information [46], underdamped Langevin dynamics [47], timedelayed Langevin systems [48], various systems [49], etc.. Recently, Hasegawa et al [50] found an uncertainty relation for the time-asymmetric observable for the system driven by a time-symmetric driving protocol using the steady state fluctuation theorem.…”
Section: Introductionmentioning
confidence: 97%
“…A connection between discrete and continuous time uncertainty relations is shown in [34]. One can also see similar uncertainty relations in the context of discrete processes [35], multidimensional systems [36], Brownian motion in the tilted periodic potential [37], general Langevin systems [38], molecular motors [39], run and tumble processes [40], biochemical oscillations [41], interacting oscillators [42], effect of magnetic field [43], linear response [44], measurement and feedback control [45], information [46], underdamped Langevin dynamics [47], timedelayed Langevin systems [48], various systems [49], etc.. Recently, Hasegawa et al [50] found an uncertainty relation for the time-asymmetric observable for the system driven by a time-symmetric driving protocol using the steady state fluctuation theorem.…”
Section: Introductionmentioning
confidence: 97%
“…Our results serve as a useful tool for estimation tasks in general Langevin systems. Information inequalities have successfully been applied to derive many important thermodynamic bounds, such as the sensitivity-precision trade-off [19], a quantum TUR [41], and the speed limit [42]. Extending our approach to other classical and quantum systems or finding a hyperaccurate observable [43] would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to attaining the derived bounds, one can show that the exact equality condition cannot be attained (from the equality condition of the Cauchy-Swartz inequality) [12]. Unlike original TUR, which is saturated near equilibrium [19], attaining the derived bounds is not ensured in such regimes. As shown later, the bounds become tight for long observation times.…”
Section: A Bounds For a Full Systemmentioning
confidence: 98%
See 2 more Smart Citations